PENGARUH KONSENTRASI IAA DAN JUMLAH DAUN ENTRES TERHADAP PERTUMBUHAN SAMBUNG PUCUK BIBIT JAMBU AIR (Syzygium aqueum) VAR. LUMUT KAYEN - Saputro, Joko; Murrinie, Endang Dewi; Arini, Nindya (Fakultas Pertanian, Universitas Janabadra, 2024)
Lumut Kayen Variety Guava is a local variety of guava from Pati Regency with a greenish color, a fruit weight of 60-100 g, and a sweet taste. Research on the application of auxin and the number of entres leaves on the graft shoots of the Lumut Kayen variety has never been carried out, therefore a study was carried out to determine the effect of Indole Acetic Acid (IAA) concentration and the number of entres leaves on the growth of the graft of the Lumut Kayen variety guava shoots. The research was carried out in Jatimulyo Village, Wedarijaksa, Pati in June - August 2023. The research is a two-factor factorial experiment using a Complete Randomize Block Design. The first factor is the concentration of auxin, consisting of three levels, namely: 0, 100, and 200 ppm. The second factor is that the number of entres leaves consists of three levels, namely: 0, 2, and 4 leaves, so that 9 combinations of treatments are repeated three times. The results showed that IAA concentration had an effect on the time of bud appearance, but had no effect on the number of shoots and the number of leaves. The fastest budding time was obtained at IAA concentration treatment of 200 ppm, which was 8.22 days. The number of entres leaves affects the time of bud appearance, the number of buds, and the number of leaves. The number of 4-leaf entres gives the fastest budding time (7.65 days), the number of shoots, and the highest number of leaves at 8 weeks after grafting, which is 7.46 buds and 20.89 leaves respectively. There was no interaction between IAA concentration and the number of entres leaves on the growth of guava seedlings.